One-Pot Microwave Assisted Solid Phase Synthesis of Cyclic Imides from Cyclic Anhydrides - (ARMAN) TAHERPOUR, AVAT; KHERADMAND, KHOJASTEH (Asian Journal of Chemistry, 2010)
In this study, a simple one-pot microwave assisted solid phase synthesis of cyclic imides from cyclic anhydrides by the use of KBr as solid phase, urea and thiourea as reagents in good yield are reported.